Geological technological innovations and contributions in the exploration and development of the Shenfu coalfield - Limin FAN (Meitian dizhi yu kantan)
BackgroundThe discovery and exploration of the Shenfu coalfield (i.e., a Jurassic coalfield in northern Shaanxi Province) represent the most significant achievement in China’s coal industry during the 6th Five-Year Plan of the country, marking the onset of the strategic westward shift of China’s coal industry. The complex discovery and exploration processes of the Shenfu coalfield have yielded valuable technological innovations. A summary of advances in the geological exploration and research of this coalfield will provide significant implications and references for the geologic work and green development of major coal-producing areas in West China. AdvancesFirst, research on the coal accumulation patterns has shifted to an objective understanding of large-scale lacustrine and deltaic sedimentary environments and five continuously deposited coal seams (formations) from the early misconception of a fluvial sedimentary environment and a chicken-nest-shaped distribution of coal seams. This sift has promoted the deployment and rapid completion of reconnaissance surveys and coal prospecting. Second, coalfield exploration has shifted from the early application of prescribed norms to bold innovations in the exploration stage of the Yushen mining area. Specifically, the integrated exploration technology for coalfields in desert areas was proposed and widely applied, significantly shortening the exploration cycle, reducing exploration costs, and enhancing the control over coal seams, strata, and various geological boundaries. As a result, despite insufficient national investment in geological exploration in the late 1990s, this technology accelerated the development of the Yushen mining area. Third, the introduction of the scientific concept of water-preserved coal mining and the establishment of the corresponding scientific and technological system represent innovations in the philosophy and methods of ecological conservation in coalfield development. Groundwater level control and ecological conservation were emphasized even during the initial exploitation of the Shenfu coalfield. China’s first provincial-level monitoring and early warning network has been established for groundwater in coal mines within the coalfield, with monitoring stations covering all coal mines and planning areas in the Shenfu coalfield. This facilitates sustainable coalfield development. Fourth, the technological innovations and application in the prevention and control of water inrushes, sand collapse, land subsidence, and geofractures, as well as relevant ecological restoration, have accelerated the construction of green mining areas, creating green mines in harmonious mining areas. ImplicationsThe huge national demand creates a great opportunity for the discovery and exploration of the Shenfu coalfield. Technological innovations act as the driving force behind the exploration progress and scientific exploration of the coalfield. Furthermore, the organic industry-university-institute collaboration represents the optimal approach to technological innovations and industrial development. ProspectsThe geological technological innovation targets of the Shenfu coalfield will undoubtedly include investigating sedimentary environments using high-resolution survey methods, constructing large transparent geological models, reducing mine water production through source control for deep coal seam mining, and achieving aquifer structure protection and ecological restoration under high-intensity coal mining.